Speech Function In Insurance Advertising Slogans - Johannes Jefria Gultom; Jimmy Jimmy (Journal of Language, Literature and Teaching, 2019)
The objectives of this study was to describe the types of speech function and the reasons of using them in the insurance advertising slogan. This research used descriptive qualitative research design. The data was taken from the insurance advertising slogans in the form of sentences that belonged to the types of speech function. To collect the data, the researcher used documentary technique. Based on the analysis of the data, it could be concluded that the types of speech function in the insurance advertising slogans can be classified into statement category. The reason of using speech function in the insurance advertising slogans was mostly used to persuade to readers or customers to join with the company despite of the speech functions of some advertisements which described its content.